Pemanfaatan Bahan Organik Kirinyuh (Chromolaena odorata L.) terhadap Komponen Hasil Beberapa Varietas Cabai Besar (Capsicum annuum L.) IPB - Siti Hafsah; Putri Astuti; Erita Hayati (Universitas Teuku Umar, 2023)
One of the efforts to increase the production of large chilies is to utilize organic sources such as kirinyuh (Chromolaena odorata L.). In addition to organic materials, the use of adaptable and high-yielding seeds is also an option in the development of large chili plants. This study aims to determine the effect of giving kirinyuh organic matter and several varieties on the yield components of large chili and the interaction between the two factors. This research was conducted at Experimental Farm 2, Faculty of Agriculture, Syiah Kuala University from May-October 2022. This study used factorial Randomized Block Design (RBD) with 2 factors and 3 replications. The first factor was the dose of organic matter left (D) consisting of 4 levels, namely control (D0), 10 tons ha-1 (D1), 20 tons ha-1 (D2) and 30 tons ha-1 (D3). The second factor was the chili variety (V) consisting of 3 levels, namely F1 Gada (V1), Anies (V2) and Seloka (V3). The results showed that the dose of kirinyuh organic matter of 10 tons ha-1 was able to increase the diameter of large chili pods. Meanwhile, the dose of kirinyuh organic matter of 30 tonnes ha-1 was able to increase the number of fruits, fruit weight per plant and yield potential of large chilies. The Anies variety gave better results on the characters of fruit number, fruit weight, fruit diameter, fruit weight, stalk length and yield potential of large chili plants. While the F1 Gada variety showed better results on fruit length characters. There was no interaction between the doses of kirinyuh organic matter and chili varieties on yield components.